Institutional Ownership as Moderation Variable of Fraud Triangle on Fraudulent Financial Statement - Retno Wulandari; Agus Maulana (Jurnal ASET (Akuntansi Riset), 2022)
Deliberate misstatement in the presentation of financial statements is a form of fraud. This study was conducted to assess the risk of occurrence of financial statement events. The correlation relationship in this study is moderated by institutional ownership. This research was conducted on 128 companies selected by purposive sampling technique from 195 population. The measurement of the level of financial statement fraud is carried out using the F-score model, and using the panel data regression analysis method. The results showed that from the element of fraud, only the element of pressure which was proxied by finance had no significant effect on financial reporting practices. While the other second element is the opportunity proxied by ineffective supervision and rationalization proxied by auditor switching does not show a significant effect on the level of financial reporting. The existence of institutional ownership is only able to moderate the relationship between financial stability and financial statement fraud.